Ethnobotany: Ethnopharmacology to Bioactive Compounds - Martinez-Salinas, J (CRC Press, 2023)
Ethnobotany: Ethnopharmacology to Bioactive Compounds comprises of carefully selected studies focusing on the importance of ethnobotanical data as an effective approach towards the discovery of novel ethnopharmacological properties and bioactive compounds that characterize herbal products, pharmaceutical drugs and medicinal plants. This book incorporates therapeutic, nutritional, phytochemistry and pharmacological properties of medicinal plants, mechanisms of action and clinical trials of bioactive compounds as well as the molecular basis of the bioactive compounds from the perspective of modern phytochemistry. This book will be useful for a diverse group of readers including students, botanists, pharmacists, chemists, herbalists and those researchers interested in ethnobotany and ethnopharmacology. © 2023 José L. Martinez, Alfred Maroyi and Marcelo L. Wagner.